Consumo de sustancias psicoactivas en las conductas sexuales de riesgo en adolescentes y adultos jóvenes. - Allauca Cajamarca, Jenifer Katherine (2024)
The aim of this bibliographic research was to determine the consumption of psychoactive substances in sexual risk behaviors in adolescents and young adults. Descriptive level study, with a population of 220 scientific articles related to the study variables, obtained in different databases, the sample was selected by a non-probabilistic process by convenience, taking 45 documents that met the inclusion criteria, studies published from 2014 to 2024. Using the CRF-QS (Critical Review Form-Quantitative Studies) instrument, the methodological quality of each article was recognized. Subsequently, the information was triangulated by means of a comparative table, in which adolescents and young adults show a high rate of consumption of legal substances such as alcohol and tobacco, although marijuana is the most consumed illegal drug, followed by inhalants and cocaine. There is some discrepancy among authors on the drug of choice, with tobacco and marijuana outweighing alcohol. In addition, drug use varies according to age, with an increase in legal substances at younger ages and a high rate of narcotic drugs from the age of 14; and a simultaneous intake of multiple substances generating poly-drug use. On the other hand, inconsistencies are reflected in the sexual behavior of PAS users, finding a high rate of sexual relations under the effects of drugs, lack of condom use, as well as sexual encounters with strangers or multiple partners, an early onset of sexual activity influenced by drugs, with a negative impact on physical and mental health, according to several authors. Adolescents often use drugs to induce others to have sex. It is determined that both variables are linked, showing that most sexual encounters without protective measures are performed under the effects of these substances because they alter judgment, risk perception and decision making.